The PACTE Model for Translation Competence and Its Impact on Improving Translation Skills and Attitudes of English Majors Freshmen Students - ماجد محمدين (Faculty of Education - Port Said University, 2020)
Abstract: The aim of this study was to explore the effect of a proposed training program based on the PACTE model for translation competence on improving translation skills and attitudes towards translation of English majors' freshmen students at Port Said Faculty of Education. The instruments included a List of Translation Skills for English Majors freshmen students, a Pre-post Observation Card, and a Pre-post scale on participants' attitudes towards translation in addition to a teacher and learner guide The study sample included 69 of English Majors Freshmen students in the academic year 2018/2019, divided into two groups: the control group included (35) individuals studying in the usual traditional way, and the experimental group included (34) individuals studying according to the proposed training program. Results revealed that the PACTE Model is effective in on improving translation skills and attitudes towards translation of English majors' freshmen students at Port Said Faculty of Education. Theoretical and pedagogical implications for EFL learning and teaching are discussed.